Sistem E-Tiket Bus Menggunakan QR-Code Berbasis Website - Revicko, Julian; Supatman (Jurnal Informatika dan Komputer, 2024)
The land public transportation mode remains the main choice for the community in carrying out mobility, especially in traveling between cities and provinces. However, many users are worried because of the rampant fraud committed by irresponsible people, because of this unrest, the perpetrators of land public transportation service providers have begun to use technology in their transaction system, this aims to minimize the existence of passengers who do not have tickets and unauthorized ticket sellers. This research uses the SDLC (System Development Life Cycle) method because it can provide the approach and structure needed in system planning and development. This system was created using the PHP programming language and the CodeIgniter Framework in the development of the system. the utilization of QR Code technology on the system is as a way to encode the code on the ticket into an E-Ticket without using paper, besides aiming to increase security, the QR Code also provides efficiency in the ticket transaction process. The use of this website is also more structured because it prevents damage or loss of tickets, increases time efficiency and increases sales. The result of this research is the successful design of a bus E-Ticket system that uses a QR Code and is website-based.